The effects of high resistance-few repetitions and low resistance-high repetitions resistance training on climbing performance - Hermans, E.; Andersen, V.; Hole Saeterbakken, A. (European Journal of Sport Science, 2017)
The aim of the study was to compare the effects of different strength training intensities on climbing performance, climbing-specific tests and a general strength test. Thirty lower grade and intermediate-level climbers participated in a 10-week training programme. The participants were randomized into three groups: high resistance-few repetitions training groups (HR-FR), low resistance-high repetitions training groups (LR-HR) and a control group (CON) which continued climbing/training as usual. Post-testing results demonstrated statistical tendencies for climbing performance improvements in the HR-FR and LR-HR (p = 0.088-0.090, effect size = 0.55-0.73), but no differences were observed between the groups (p = 0.950). For the climbing-specific tests, no differences were observed between the groups (p = 0.507-1.000), but the HR-FR and LR-HR improved their time in both Dead-hang (p = 0.004-0.026) and Bent-arm hang (p < 0.001-0.002). The HR-FR and LR-HR improved their 12RM strength in pull-down (p = 0.001), but not the CON group (p = 0.250). No differences were observed in the CON group in any of the tests (p = 0.190-0.596) with the exception of improvement in Bent-arm Hang (p = 0.018). The training groups reduced their climbing sessions during the intervention compared to the CON group (p = 0.057-0.074). In conclusion, HR-FR and LR-HR training programmes demonstrated an 11% and 12% non-significant improvement in climbing performance despite a 50% reduction in climbing sessions, but improved the results in strength and climbing-specific tests. None of the training intensities was superior compared to the others.